The governance of religious diversity in stateless nations: the case of Catalonia. Issue 1 (2nd January 2016) - Griera, Mar
ABSTRACT: Academic literature dealing with the governance of religious diversity in Europe has gained saliency in recent years. However, most existing research is based on state-level policies, while the role of regional government is receiving far less attention. To address this lacuna, this article focuses attention on the role of the regional government in the regulation of religious diversity in Catalonia. The article reflects on the increasing relevance of religious affairs in the Catalan policy agenda and examines the emergence and configuration of a specific, distinct and prominent regional policy programme on religious diversity. The case of Catalonia is especially relevant since its ongoing nation-building project bestows additional complexity and strategic relevance on the policy approach towards religious issues.